Penyakit Hawar Pelepah (Rhizoctonia solani) pada Padi dan Taktik Pengelolaannya - Bambang Nuryanto (Jurnal Perlindungan Tanaman Indonesia, 2017)
Rice sheath blight disease caused by Rhizoctonia solani Kuhn (AG-1), is one of diseases currently growing and widespread in rice-producing areas in Indonesia. Widely planting of short-type and many tillers rice varieties with high doses fertilized, especially urea, can increase the severity of sheath blight disease. Sheath blight disease is becoming increasingly important role in the rice production system, especially in intensive rice farming. Therefore, it is necessary to analyze epidemic components affecting sheath blight development to determine their management strategies. The sheath blight disease is observed to develop more severe in low areas (0−200 m above sea levels) than in the moderate and high areas, severity of disease is seen to increase in short-type many tillers rice varieties. Initial inoculum are sclerotia and the mycelia in plant debris that have an important role in the rice sheath blight development. However, sclerotia may fail to germinate due colonized by various kinds of antagonistic bacteria in the soil. Bacteria that are antagonistic to R. solani can be isolated from paddy soil containing compost. Mature compost can suppress germination of sclerotia of R. solani by 14%, while in the mature compost enriched with antagonistic bacteria can suppress the germination of sclerotia by 28%. Relative humidity and temperature around the plant affect the development of rice sheath blight disease. Relative humidity decreased 2.8% when watering is only done by flooding the trench around, and decreased by 4.4% when flooding of land only 1 time per week. Sheath blight control by implementing some components in an integrated epidemic have higher chances of success in suppressing the disease development.